Variasi Sukrosa dalam Pembuatan Minuman Probiotik Buah Nipah (Nypa fruticans) dengan Menggunakan Starter Lactobacillus fermentum InaCCB1295 - Jenius Raden Angkasa; Usman Pato (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2021)
The purpose of this research was to evaluate the effect of variation sucrose using starter Lactobacillus fermentum InaCC B1295 on the quality of probiotic drink of nipah fruit. This research was conducted experimentally using Completely Randomized Design with five treatments and three replications. The treatments in this study were PN1 (without addition of sugar), PN2 (addition of 2% sugar), PN3 (addition of 4% sugar), PN4 (addition of sugar 6%) and PN5 (addition of sugar 8%). Data obtained were statically analyzed by analysis of variance (ANOVA) and continued with Duncan’s New Multiple Range Test (DNMRT) at level 5%. The results show that variation of sucrose concentration significantly affected pH value, total lactic acid, total lactic acid bacteria, total sugar, ash, colour, consistency, flavour, taste and overall acceptance of probiotic drink. The best treatment was PN5 (addition of 8% sugar), with pH 3.41, total lactic acid 0.51%, total LAB 10.23 cfu/ml, total sugar 10.36%, and ash content 0.08%. The probiotic drink of PN5 treatment was favored by panelists with cloudy white colour (3.53), nipah fruit and acidic flavour (3.77), rather thick texture (3.60), sweet taste (3.86). Overall assessment hedonik test of nipah fruit probiotic drink was preferred by the panelists.Keywords: probiotics, nipah fruit, Lactobacillus fermentum InaCC B1295.